A revision of the Palaearctic species of Reikosiella (Hirticauda) (Hymenoptera, Eupelmidae) - Fusu, Lucian (Zootaxa, 2013)
The Palaearctic species of Reikosiella Yoshimoto, subgenus R. (Hirticauda Bouček), are revised. Illustrated keys are given to identify females of the ten recognized species and all known males. In addition to R. (Hirticauda) hungarica (Erdős), previously the only formally recognized Palaearctic species, two species are newly transferred to the genus and subgenus, R. (Hirticauda) bolivari (Kalina) comb. nov. and R. (Hirticauda) rostrata (Ruschka) comb. nov., both from Eupelmus Dalman. Seven species are described as new: R. (Hirticauda) andriescui sp. nov. from Canary Islands, R. (Hirticauda) gordoni sp. nov. and R. (Hirticauda) graeca sp. nov. from Greece, R. (Hirticauda) vanharteni sp. nov. from United Arab Emirates, and R. (Hirticauda) cornuta sp. nov., R. (Hirticauda) koreana sp. nov., and R. (Hirticauda) tripotinorum sp. nov. from Korea. A lectotype is designated for Eupelmus rostratus Ruschka. Host records are critically discussed for sev-eral species in the light of their new generic placement.